IMPLEMENTATION OF ONLINE COLLABORATIVE LEARNING IN DATABASE SYSTEMS COURSES - Nurdin Ibrahim; Sriasih; Suyitno Muslim (Journal of Islamic, Social, Economics and Development, 2022)
This study aims to determine the effectiveness of the implementation of online collaborative learning in the Database System Course. Respondents in this study were secondsemester students in the Undergraduate Program, Faculty of Information and Communication Technology, Mataram University of Technology. The respondents used were 25 students, who were taken from one class in the Department of Informatics Engineering. Techniques for Problem Solving were chosen as a collaborative technique by choosing one of the techniques in it, namely Send-A-Problem. Send-A-Problem is a technique of solving a problem in groups, then forwarding the problem and its solution to the closest group who then does the same thing; the last group will evaluate all these solutions. From the results of the research conducted, it was obtained that the average value of students from the previous 58.52 rose to 80.36 after the implementation. There is a difference in the increase in the value of the Database System course exam of 21,840. This indicates that student learning outcomes increase if learning is done online collaboratively. The results of the t-test also show the value of Sig. (2-tailed) is 0.000 < 0.05, so it can be concluded that there is an average difference between the learning outcomes before and after, meaning that there is an influence on the implementation of online collaborative in the Database System Course. The online collaborative is suggested as a way to improve learning outcomes, which of course are not bound by space and time.